Impact of the severity of obesity on microalbuminuria in obese normotensive nondiabetic individuals - Minoo, Farzanehsadat (J Renal Inj Prev, 2015)
Introduction: Microalbuminuria has been now recognized as the most important risk factor for the increased morbidity and mortality in the obese population. Objectives: We aimed to know whether severity of obesity is associated with the presence of renal injury while microalbuminuria acts, independent of other risk factors as hypertension and diabetes mellitus. Patients and Methods: The current cross-sectional study was conducted on consecutive obese normotensive nondiabetic individuals. Two groups of adult individuals were selected as controls comprised of 161 obese adults with body mass index (BMI) 30-35 kg/m(2) and 25 very obese adults as cases with BMI more than 35 kg/m(2). Microalbuminuria was defined as abnormal urinary albumin to creatinine ratio (UACR) more than 30 mg/g of creatinine. Results: No significant differences in serum creatinine level, urinary albumin concentration, as well as UACR between obese and very obese individuals was seen. Using Pearson correlation coefficient analysis, no significant correlation was observed between BMI and parameters of renal function. Microalbuminuria was more prevalent in very obese individuals compared with obese group (24.0% versus 9.9%, P = 0.043) in univariate analysis. Conclusion: Severe obesity compared with milder obesity status cannot predict the occurrence of increased urinary albumin excretion and microalbuminuria.